The Chains of Ferroptosis Interact in the Whole Progression of Atherosclerosis - Wan X; Zhang H; Tian J; Hao P; Liu L; Zhou Y; Zhang J; Song X; Ge C (Dove Medical Press, 2023)
Xueqi Wan,* Huan Zhang,* Jinfan Tian,* Peng Hao, Libo Liu, Yuquan Zhou, Jing Zhang, Xiantao Song, Changjiang Ge Department of Cardiology, Beijing Anzhen Hospital, Capital Medical University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Changjiang Ge; Xiantao Song, Email cjge1116@163.com; song0929@mail.ccmu.edu.cnAbstract: Atherosclerosis (AS), a category of cardiovascular disease (CVD) that can cause other more severe disabilities, increasingly jeopardizes human health. Owing to its imperceptible and chronic symptoms, it is hard to determine the pathogenesis and precise therapeutics for AS. A novel type of programmed cell death called ferroptosis was discovered in recent years that is distinctively different from other traditional cell death pathways in morphological and biochemical aspects. Characterized by iron overload, redox disequilibrium, and accumulation of lipid hydroperoxides (L-OOH), ferroptosis influences endothelial cells, vascular smooth muscle cells (VSMCs), and macrophages, as well as inflammation, partaking in the pathology of many cardiovascular diseases such as atherosclerosis, stroke, ischemia-reperfusion injury, and heart failure. The mechanisms behind ferroptosis are so sophisticated and interwoven that many molecules involved in this procedure are unknown. This review systematically depicts the initiation and modulation of ferroptosis and summarizes the contribution of ferroptosis to AS, which may open a feasible approach for target treatment in the alleviation of AS progression.Keywords: ferroptosis, iron overload, oxidation, lipid peroxidation, atherosclerosis